The Effort of Islamic Education to Improve the Children’s Morality on Elementary School on Petaling Mendo Barat - Sumar Sumar (Tarbawy : Jurnal Pendidikan Islam, 2018)
The Teachers of Islamic education today are often confused with the behavior of learners who are increasingly worried about morals. Petaling villages, especially teachers often complain about the behavior of elementary school children who are not praised, are they will not the obey the teacher’s, rebuked, fighting even some who up against the teacher. The purpose of this study is to reduce or at least the development of negative morals in elementary school. As for the result of this research was found there are three the main factors that cause deterioration attitude a son, namely.1. Factors family 2.Environmental factor and 3.Factors the act of government on violence children.While the results of the efforts the teacher's Islamic education of the three elements are is, from the family: teachers diligent socialization the parents with appeal more attention to their children each especially in intercourse and learn. Edify their children. From the environment: teachers giving an appeal to school tuition that is not weary of he warns against careful in sociable.From the act of the government: the teachers continue to trying to find methods creatif capable of comply with the act the government about child protection and regulations.